Performance Optimization of ZnO based Thin Film Transistor for Future Generation Display Technology - Singh A.K.; Kharche V.V.; Chakrabarti P. (My University, 2025)
Zinc oxide based thin-film transistors (TFT) built with an Al2O3insulator layer have been analyzed on Silvaco ATLAS™ 2D simulator in order to optimize their performance for application in display systems. We have optimized the geometry of the structure by varying the oxide thickness and semiconductor channel for achieving high performance switching application in display technology. The study revealed that the device can be successfully optimized to achieve a very high value of on-off ratio of \sim 2.78\times 10^{8} to provide a better driving capability and yet maintaining a low sub-threshold voltage of 0.55 V/decade ensuring high speed of operation. The high performance ZnO based device proposed to be built on Al2O3insulator will make it cost-effective for large display systems. © 2017 IEEE.